2021
DOI: 10.1002/hipo.23295
|View full text |Cite
|
Sign up to set email alerts
|

Goal‐directed interaction of stimulus and task demand in the parahippocampal region

Abstract: The hippocampus and parahippocampal region are essential for representing episodic memories involving various spatial locations and objects, and for using those memories for future adaptive behavior. The "dual-stream model" was initially formulated based on anatomical characteristics of the medial temporal lobe, dividing the parahippocampal region into two streams that separately process and relay spatial and nonspatial information to the hippocampus. Despite its significance, the dual-stream model in its orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 202 publications
0
14
0
Order By: Relevance
“…We hypothesize that in addition to a figure, which is processed as an object, the ventral pathway would process a background, which might have been observed as a scene-selective response in previous studies ( Epstein and Kanwisher, 1998a ; Kornblith et al, 2013 ; Vaziri et al, 2014 ). Consistent with this idea, recent rodent studies have reported that the PRC of the ventral pathway-MTL stream contributes to spatial or visual scene processing as well as conventional item processing ( Fiorilli et al, 2021 ; Lee et al, 2021 ).…”
Section: Scene-selective Response In the Ventral Pathway-medial Temporal Lobe Streammentioning
confidence: 69%
“…We hypothesize that in addition to a figure, which is processed as an object, the ventral pathway would process a background, which might have been observed as a scene-selective response in previous studies ( Epstein and Kanwisher, 1998a ; Kornblith et al, 2013 ; Vaziri et al, 2014 ). Consistent with this idea, recent rodent studies have reported that the PRC of the ventral pathway-MTL stream contributes to spatial or visual scene processing as well as conventional item processing ( Fiorilli et al, 2021 ; Lee et al, 2021 ).…”
Section: Scene-selective Response In the Ventral Pathway-medial Temporal Lobe Streammentioning
confidence: 69%
“…Our findings do not fit the traditional model and suggest that modifications of the model are in order. Specifically, recent studies have raised the possibility that parahippocampal region areas may not be as sharply segregated as once thought (Hunsaker et al, 2013, Knierim et al, 2014, Park et al, 2017, Yoo and Lee, 2017, Lee et al, 2021. Furthermore, a recent study suggested that the POR also projects heavily to the LEC and that the connectivity between the POR and MEC is not as prominent as previously thought (Doan et al, 2019).…”
Section: The Fc Has Place Cells Despite the Fact That Its Major Inputs Originate From Non-spatial Parahippocampal Regionsmentioning
confidence: 96%
“…Hence the involved functional architecture differs for multimodal objects and scene memories due to biased pathways of information processing (cf. Fiorilli et al, 2021 ; Lee et al, 2021 ; but note the described profound overlap as well). Under healthy conditions, multimodal representations may enhance memorability because a memory can be accessed via multiple ways (e.g.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 94%
“…In Alzheimer's disease particularly multimodal representation areas like the perirhinal cortex (cf. Fiorilli et al, 2021 ; Bussey et al, 2005 ; Lee et al, 2021 ) are affected early on, presumably leading to an increased vulnerability for certain object memories. Another appealing mechanism that may determine differential memorability effects in Alzheimer's disease are attentional and perceptual mechanisms.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%